2016
DOI: 10.1016/j.jjcc.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Association between dental caries and out-of-hospital cardiac arrests of cardiac origin in Japan

Abstract: While oral hygiene is important in all age groups, it may be particularly associated with OHCAs of cardiac origin in males over 65 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Oral health variables such as the presence of dental caries, periodontitis, periapical infections, tooth loss and the number of teeth significantly ( P -values < .05) increased the risk of cardiovascular diseases among the elderly population in 7 studies after adjusting for confounding variables such as smoking status, obesity, diabetes, and sex. 23,45,46,48,118,120,122 Schillinger et al suggested oral hygiene and dental status, particularly edentulousness, as significant predictors of progression of carotid stenosis, where edentulous Australian elderly aged between 62 and 76 years had twice (adjusted OR = 2.10, 95% CI: 1.06-4.16) the risk for disease progression when compared to those with teeth. 118 With respect to periodontitis, Chen et al reported that Japanese elderly having periodontitis aged between 53 and 73 years with periodontitis had 5 (OR = 5.45, 95%CI: 1.57-18.89) times the risk for peripheral arterial disease (PAD) compared to those with healthy periodontium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral health variables such as the presence of dental caries, periodontitis, periapical infections, tooth loss and the number of teeth significantly ( P -values < .05) increased the risk of cardiovascular diseases among the elderly population in 7 studies after adjusting for confounding variables such as smoking status, obesity, diabetes, and sex. 23,45,46,48,118,120,122 Schillinger et al suggested oral hygiene and dental status, particularly edentulousness, as significant predictors of progression of carotid stenosis, where edentulous Australian elderly aged between 62 and 76 years had twice (adjusted OR = 2.10, 95% CI: 1.06-4.16) the risk for disease progression when compared to those with teeth. 118 With respect to periodontitis, Chen et al reported that Japanese elderly having periodontitis aged between 53 and 73 years with periodontitis had 5 (OR = 5.45, 95%CI: 1.57-18.89) times the risk for peripheral arterial disease (PAD) compared to those with healthy periodontium.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles evaluated the risk of cardiovascular diseases due to poor oral health. 23,26,[33][34][35]45,46,48,[118][119][120][121][122] The majority of the studies were prospective cohort, 5 studies were case-control, 33,45,48,119,120 and only 1 study was a retrospective cohort. 46 Outcomes for cardiovascular diseases included stroke, cardiac arrest, hypertension, coronary heart disease, non-fatal ischemic stroke, acute myocardial infarction, cerebrovascular disease, peripheral artery disease, carotid stenosis, pulmonary embolism, and heart failure.…”
Section: List Of Outcomesmentioning
confidence: 99%
“…[7] The cause of OHCA-CA is also an important public health problem. We have reported the associations between OHCA-CA and dental caries, [8] seafood consumption, [9] and consumption of carbonated beverages [10] using the All-Japan Utstein Registry. Cold month in the toilet, [11] severe emotional stress, [12,13] climate, [14][15][16] and temperature [17][18][19] have also been reported to be causes of OHCA-CA in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies evaluated the prevalence or severity of dental caries as a risk factor for CVD [ 8 , 41 , 42 , 67 , 68 , 69 , 70 , 71 ]. The authors concluded that caries, especially in the advanced/severe stage, were significantly associated with increased CHD risk.…”
Section: Discussionmentioning
confidence: 99%